Ceramic copper-clad plate and preparation method thereof

By using high-entropy alloy compound solder paste and zirconia ceramic matrix, combined with screen printing and vacuum brazing technology, the problem of plate breakage and blackening during the preparation of ceramic copper clad plate is solved, and the reliability and thermal conductivity of the product are improved.

CN119815682APending Publication Date: 2025-04-11BYD CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411999628.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

During the preparation process, existing ceramic copper clad plates are prone to breaking the plate and the ceramics turn black after etching, resulting in poor reliability.

Method used

Ceramic copper clad plates were prepared by screen printing and vacuum brazing using solder paste including high entropy alloy compounds and ceramic matrix containing 6%-12% zirconia.

Benefits of technology

It effectively avoids the interruption of the plate during the preparation of ceramic copper clad plate and the blackening of the ceramic after etching, improves the reliability of ceramic copper clad plate and reduces thermal resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119815682A_ABST
    Figure CN119815682A_ABST
Patent Text Reader

Abstract

The ceramic copper-clad plate comprises a welding layer, the welding layer is made of welding paste, the welding paste comprises a high-entropy alloy compound, the chemical formula of the high-entropy alloy compound is CuaAlbSncNidPeMofTig, g is larger than or equal to 7 and smaller than or equal to 25 wt%, and a + b + c + d + e + f + g is equal to 100%; the ceramic matrix comprises zirconium oxide with the mass fraction of 6%-12%. According to the scheme provided by the invention, the conditions of plate breakage in the preparation process of the ceramic copper-clad plate and blackening of the etched ceramic can be avoided, and the reliability of the ceramic copper-clad plate can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electronic power technology, and in particular to a ceramic copper clad laminate and a method for preparing the ceramic copper clad laminate. Background Art

[0002] Ceramic copper clad laminate has the advantages of high strength, good chemical stability and high thermal conductivity. It is an ideal matrix material for power devices. It can provide physical support for chips, connect circuits, and form heat dissipation channels.

[0003] In the related technology, direct copper bonding technology (DBC) and active metal brazing technology (AMB) are generally used to achieve the connection between ceramics and copper foil. However, during the preparation process using the AMB process, problems such as board breakage during the process, blackening of the ceramic after etching of the solder layer, and poor reliability may easily occur due to the high activity of titanium and the violent reaction with the ceramic.

[0004] Therefore, the current ceramic copper clad laminate and the method for preparing the ceramic copper clad laminate still need to be improved. Summary of the invention

[0005] In order to solve or partially solve the problems existing in the related art, the present application provides a ceramic copper clad laminate and a method for preparing a ceramic copper clad laminate, which can avoid the breakage of the ceramic copper clad laminate during the preparation process and the blackening of the ceramic after etching, and can improve the reliability of the ceramic copper clad laminate.

[0006] The first aspect of the present application provides a ceramic copper-clad laminate, the ceramic copper-clad laminate comprising: a solder layer, the solder layer is made of solder paste, the solder paste comprises a high entropy alloy compound, the chemical formula of the high entropy alloy compound is: Cu a Al b Sn c Ni d P e Mo f Ti g , wherein 7≤g≤25wt%, and a+b+c+d+e+f+g=100%; a ceramic matrix, wherein the ceramic matrix comprises zirconium oxide with a mass fraction of 6%-12%.

[0007] In combination with the first aspect, in a possible implementation of the first aspect, in the high entropy alloy compound, 35≤a≤65wt%, 10≤b≤35wt%, 10≤c≤25wt%, 0.1≤d≤10wt%, 0.05≤e≤3wt%, and 0≤f≤10wt%.

[0008] In combination with the first aspect, in a possible implementation of the first aspect, the solder paste also includes a binder, and the binder includes 75-98wt% of a solvent, 0.1-20wt% of a dispersant, 0.05-15wt% of a thickener, 0.05-3wt% of a surfactant and 0-10wt% of a thixotropic agent.

[0009] In combination with the first aspect, in a possible implementation of the first aspect, the solder paste satisfies any one of the following conditions: the solvent includes one or more of pineol, tributyl citrate, diethylene glycol butyl ether and diethylene glycol butyl ether acetate; the dispersant includes one or more of oleic acid, stearic acid, and polyethylene glycol; the thickener includes one or more of ethyl cellulose, acrylic resin, cyclodextrin, and alkanes; the surfactant includes one or more of Tween 20, Span 80, and sodium dodecylbenzene sulfonate; the thixotropic agent includes one or more of polyamide wax, modified polyurea, and hydrogenated castor oil.

[0010] In combination with the first aspect, in a possible implementation of the first aspect, the mass fraction of the high entropy alloy compound in the solder paste is 60%-95%, and the mass fraction of the binder is 5%-40%.

[0011] In combination with the first aspect, in a possible implementation manner of the first aspect, the melting point range of the solder paste is 700-960° C., and the particle size range of the solder paste is 0.3-60 um.

[0012] In combination with the first aspect, in a possible implementation manner of the first aspect, the thickness of the ceramic substrate is 0.2-2 mm.

[0013] In combination with the first aspect, in a possible implementation of the first aspect, setting the copper layer includes: providing a copper-containing material; the thickness of the copper-containing material is 0.1 mm-5 mm, wherein the copper-containing material is selected from one or more of a copper sheet, a high thermal conductivity copper-based composite material and a high thermal conductivity copper-based alloy.

[0014] The second aspect of the present application provides a method for preparing a ceramic copper clad laminate, comprising providing a ceramic substrate; disposing a solder paste on the surface of the ceramic substrate, wherein the solder paste comprises a high entropy alloy compound; disposing a copper layer on the surface of the solder paste on a side away from the ceramic substrate, and performing a brazing process to obtain the ceramic copper clad laminate.

[0015] In combination with the second aspect, in a possible implementation of the second aspect, the process of setting the solder paste on the surface of the ceramic substrate is screen printing, wherein the screen printing thickness of the solder paste set on the surface of the ceramic substrate by screen printing is 6-25um; the brazing treatment is a vacuum brazing treatment, wherein the temperature of the vacuum brazing treatment is 850-1060°C, and the time of the vacuum brazing treatment is 0.5-3h.

[0016] The technical solution provided by this application may have the following beneficial effects:

[0017] The ceramic copper-clad laminate and the preparation method of the ceramic copper-clad laminate of the present application, the ceramic copper-clad laminate comprises a solder layer, the solder layer is made of solder paste, the solder paste comprises a high entropy alloy compound, the chemical formula of the high entropy alloy compound is: Cu a Al b Sn c Ni d P e Mo f Ti g , wherein 7≤g≤25wt%, and a+b+c+d+e+f+g=100%; a ceramic matrix, the ceramic matrix includes 6%-12% by mass of zirconium oxide, which can avoid the breakage of the ceramic copper clad laminate during the preparation process and the blackening of the ceramic after etching, and can improve the reliability of the ceramic copper clad laminate.

[0018] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The above and other objects, features and advantages of the present application will become more apparent by describing in more detail exemplary embodiments of the present application in conjunction with the accompanying drawings, wherein the same reference numerals generally represent the same components in the exemplary embodiments of the present application.

[0020] Figure 1 It is a schematic diagram of a process for preparing a ceramic copper-clad laminate shown in an embodiment of the present application;

[0021] Figure 2 It is a schematic diagram of the structure of the ceramic copper-clad plate after etching shown in the embodiment of the present application;

[0022] Figure 3 It is a schematic diagram of the structure of the welding layer of the ceramic copper clad laminate shown in the embodiment of the present application. DETAILED DESCRIPTION

[0023] The embodiments of the present application will be described in more detail below with reference to the accompanying drawings. Although the embodiments of the present application are shown in the accompanying drawings, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to make the present application more thorough and complete, and to fully convey the scope of the present application to those skilled in the art.

[0024] The terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The singular forms of "a", "a", "an" and "the" used in this application and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used in this article refers to and includes any or all possible combinations of one or more associated listed items.

[0025] It should be understood that although the terms "first", "second", "third", etc. may be used in this application to describe various information, this information should not be limited to these terms. These terms are only used to distinguish the same type of information from each other. For example, without departing from the scope of this application, the first information may also be referred to as the second information, and similarly, the second information may also be referred to as the first information. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined.

[0026] In the related technology, the ceramic substrate materials commonly used in the field of electronic device packaging technology are alumina, toughened alumina, aluminum nitride, silicon nitride, silicon carbide, etc. Among them, although alumina ceramics do not have the good thermal conductivity and thermal expansion coefficient of aluminum nitride and silicon nitride, they have good mechanical strength, good insulation performance, low dielectric loss, and bending strength greater than or equal to 300MPa. In particular, the bending strength of the toughened zirconium oxide is ≥500MPa, and the production cost is low. It is widely used in microelectronic packaging, such as LED packaging, some power semiconductor packaging, etc.

[0027] The industry's copper-clad aluminum substrates mostly use the DBC process, which has the characteristics of low ultrasonic yield (about 90%) and poor reliability. The aluminum-clad aluminum substrates prepared by the AMB process are prone to broken boards due to differences in the content and distribution of active elements, and black etching due to differences in the zirconium oxide content in ZTA ceramics. These problems limit the development and commercial use of copper-clad aluminum substrates with high yield and reliability. The copper-clad boards made by the traditional DBC process have a single interface component, high brittleness, and low tolerance to cold and heat; technical processes such as atmospheric plasma spraying are inefficient, and it takes time to spray to the required metal layer thickness, which is not convenient for mass production and has high indirect costs; the oxygen content of raw materials is strictly required, and the current carrying capacity and heat dissipation capacity are low, not as good as oxygen-free pure copper.

[0028] In the previous process, effective bonding of copper and ceramics can be achieved through Cu, Sn, Ti, etc., and the titanium content can be reduced by controlling the Sn content, which leads to a decrease in the thermal conductivity of the solder layer, which is directly reflected in the increase in the thermal resistance of the copper clad laminate. However, excessive Ti elements in the preparation process will make Ti highly active, resulting in a violent reaction between titanium and ceramics, which is prone to problems such as broken boards and blackening of ceramics after etching of the solder layer. Therefore, it is necessary to change the manufacturing method to reduce the probability of broken boards and avoid the problem of blackening of ceramics after etching of the solder layer.

[0029] In view of the above problems, the embodiments of the present application provide a ceramic copper clad laminate and a method for preparing the ceramic copper clad laminate, which can avoid the breakage of the ceramic copper clad laminate during the preparation process and the blackening of the ceramic after etching, and can improve the reliability of the ceramic copper clad laminate.

[0030] The technical solution of the embodiments of the present application is described in detail below with reference to the accompanying drawings.

[0031] In one aspect of the present application, the present application proposes a ceramic copper-clad laminate, the ceramic copper-clad laminate comprising: a solder layer, the solder layer is made of solder paste, the solder paste comprises a high entropy alloy compound, the chemical formula of the high entropy alloy compound is: Cu a Al b Sn c Ni d P e Mo f Ti g , wherein 7≤g≤25wt%, and a+b+c+d+e+f+g=100%; a ceramic matrix, the ceramic matrix includes 6%-12% by mass of zirconium oxide, and by controlling the Ti content in the solder paste, the problem of brittle plate breakage due to excessive stress release in the process can be reduced; and titanium has high activity and reacts with zirconium oxide lattice oxygen to generate TiO in addition to reacting with alumina. x , ZrO 2-x . And ZrO 2-x It appears black. The more zirconium oxide content, the blacker the ceramic will turn after etching. Therefore, controlling the Ti content can improve the yield in the product batch and further reduce the cost.

[0032] Specifically, unlike traditional alloys that use a certain element as the matrix, high entropy alloys are alloys composed of 5 or more elements (generally no more than 13) in equiatomic or non-equiatomic ratios. This alloy has a high mixing entropy, and its huge lattice distortion is caused by the difference in the characteristics of the added elements. High mixing entropy can make the alloy easily form a relatively stable solid solution structure, thereby increasing the resistance to atomic migration and achieving an increase in the difficulty of diffusion. Due to the combined characteristics of different atoms and concentrations, high entropy alloys exhibit a cocktail effect of performance regulation. High entropy alloy compounds have a multi-principal high mixing entropy effect, which can reduce the content of intermetallic compound phases, improve the plasticity of the solder layer, improve reliability, and increase thermal conductivity and reduce thermal resistance. The use of multi-principal high mixing entropy effect can make the copper clad laminate have good plasticity and high reliability when withstanding cold and hot shocks; there are few intermetallic compounds, low phonon thermal conductivity of the heterogeneous interface, high electronic thermal conductivity, and high overall thermal conductivity.

[0033] Specifically, in the preparation of the high entropy alloy compound layer, when the content of the active element Ti in the high entropy alloy powder is 0, an active material containing Ti, such as pure titanium powder or titanium hydride, can be added during the production process. The titanium hydride can be ultrafine titanium hydride prepared by high-energy ball milling in a vacuum or inert atmosphere, so that the obtained high entropy alloy compound contains the Ti element. The high entropy alloy compound can provide the active element Ti in the process of preparing the ceramic copper-clad laminate. The particle size of the titanium hydride is less than or equal to 30 μm, preferably 2-15 μm, and more preferably 3-10 μm.

[0034] Furthermore, in the high entropy alloy compound, 35≤a≤65wt%, 10≤b≤35wt%, 10≤c≤25wt%, 0.1≤d≤10wt%, 0.05≤e≤3wt%, and 0≤f≤10wt%.

[0035] In one possible embodiment, the chemical formula of the high entropy alloy compound is: Cu a Al b Sn c Ni d P e Mo f Ti g , wherein 40≤a≤55wt%, 15≤b≤25wt%, 12≤c≤18wt%, 0.5≤d≤3wt%, 0.1≤e≤1.5wt%, 0.5≤f≤2wt%, 7≤g≤12wt%, and a+b+c+d+e+f+g=100%.

[0036] In a possible embodiment, the solder paste also includes a binder, which includes 75-98wt% of a solvent, preferably 80%-95wt% of the solvent, and more preferably 85-90wt% of the solvent; 0.1-20wt% of a dispersant, preferably 1-10wt% of the dispersant, and more preferably 2-6wt% of the dispersant; 0.05-15wt% of a thickener, preferably 1-10wt% of the thickener, and more preferably 2-6wt% of the thickener; 0.05-3wt% of a surfactant, preferably 0.5-2wt% of the surfactant, and more preferably 1-2wt% of the surfactant; 0-10wt% of a thixotropic agent, preferably 0.5-5% of the thixotropic agent, and more preferably 0.8-4wt% of the thixotropic agent.

[0037] In a possible embodiment, the solder paste satisfies any one of the following conditions: the solvent includes one or more of pineol, tributyl citrate, diethylene glycol butyl ether and diethylene glycol butyl ether acetate; the dispersant includes one or more of oleic acid, stearic acid, and polyethylene glycol; the thickener includes one or more of ethyl cellulose, acrylic resin, cyclodextrin, and alkane; the surfactant includes one or more of Tween 20, Span 80, and sodium dodecylbenzene sulfonate; the thixotropic agent includes one or more of polyamide wax, modified polyurea, and hydrogenated castor oil.

[0038] In one possible implementation, the mass fraction of the high entropy alloy compound in the solder paste is 60%-95%, preferably, the mass fraction of the high entropy alloy compound is 75%-90%, and the mass fraction of the binder is 5%-40%, preferably, the mass fraction of the binder is 10%-25%.

[0039] In this application, all the numbers disclosed herein are approximate values, regardless of whether the words "about" or "approximately" are used. The value of each number may vary by less than 10% or a reasonable difference considered by those skilled in the art, such as 1%, 2%, 3%, 4% or 5%.

[0040] Specifically, the binder in the solder paste can be prepared by mixing the solvent, surfactant, dispersant, thickener, and thixotropic agent by heating in an electromagnetic water bath, stirring, and filtering to make them uniform.

[0041] In a possible implementation, the melting point of the solder paste is in the range of 700-960°C, preferably, the melting point of the solder paste is in the range of 750-900°C, and more preferably, the melting point of the solder paste is in the range of 750-820°C. The particle size of the solder paste is in the range of 0.3-60um, preferably, the particle size is in the range of 0.8um-25um, and more preferably, the particle size is in the range of 0.8-20um. The particle size distribution range is (D90-D10) / D50: 1.2-2.3, preferably, the particle size distribution range is 1.5-2.2, and more preferably, the particle size distribution range is 1.7-2.1. The solder paste has a suitable melting point and a suitable particle size distribution. The suitable particle size distribution can help improve the compactness of the silk screen printing area and facilitate the volatilization and exhaust of the organic carrier. The silk screen thickness can affect the thickness of the final solder layer, and finally improve the reliability of the ceramic copper clad laminate.

[0042] In one possible embodiment, the viscosity range of the solder paste is 20Pas-500Pas, the preferred viscosity range is 40Pas-150Pas, and the more preferred viscosity range is 60Pas-90Pas. Solder paste with a suitable viscosity range is conducive to silk screen printing, can improve silk screen printing performance, and make the formed surface to be soldered have better uniformity and leveling.

[0043] In a possible embodiment, the ceramic copper clad laminate further includes a copper layer, which is made of a copper-containing material having a thickness of 0.1 mm to 5 mm, and the copper-containing material is selected from one or more of a copper sheet, a high thermal conductivity copper-based composite material, and a high thermal conductivity copper-based alloy.

[0044] In another aspect of the present application, the present application proposes a method for preparing a ceramic copper-clad laminate, comprising: providing a ceramic substrate; placing a solder paste on the surface of the ceramic substrate; placing a copper layer on the surface of the solder paste away from the ceramic substrate, and performing a brazing process to obtain a ceramic copper-clad laminate. Thus, good welding between the ceramic substrate and the copper layer can be achieved, and a ceramic copper-clad laminate with excellent performance can be obtained.

[0045] Specifically, see Figure 1 , the preparation method of the ceramic copper clad laminate may include the following steps:

[0046] S100: providing a ceramic substrate.

[0047] According to some embodiments of the present application, a ceramic matrix is ​​provided in this step, and the type of the ceramic matrix is ​​not particularly limited. For example, the ceramic matrix may include ceramic materials such as alumina, zirconia-toughened alumina ceramics, silicon nitride, aluminum nitride, and silicon carbide. Specifically, the thickness of the alumina ceramic may be 0.2-2 mm, preferably 0.32-1.5 mm, and the alumina ceramics preferably contain 99%, 96%, or 95% alumina. The zirconium oxide content in the zirconia-toughened alumina ceramics may be 6%-12%, preferably 7%-9%.

[0048] According to some embodiments of the present application, the high entropy alloy compound in the solder paste can be prepared by the following method, using an electromagnetic vacuum melting process to repeatedly melt the high entropy alloy at 1200°C-1500°C for multiple times to make it uniform, and then using a vacuum gas atomization method to make powder, wherein the high entropy alloy compound after gas atomization needs to pass through an extremely cold zone to enter a powder collection container. Among them, the extremely cold zone is cooled at a rate of 80°C-300°C / s, and the cooling rate is preferably 150-300°C / s, and more preferably 150-200°C / s. The high-speed gas can be nitrogen, argon, or a mixture of the two, with a purity of ≥99.9999%. The collected powder is screened with a graded vibrating screen at 500-3000Hz to obtain a suitable particle size to obtain a suitable high entropy alloy compound.

[0049] The adhesive can be prepared by the following method: first, slowly add the solvent into an electromagnetic water bath, slowly stir at 30-100 rpm while heating to 60-120°C, then add the surfactant, dispersant, thickener, and thixotropic agent in sequence, and after each component is stirred at 300-600 rpm for 15 minutes, add other components in sequence, and repeat this step until the above additives are added, then stir and mix at a speed of 800-1500 rpm for 3 hours, then stir at a speed of 500 rpm for 1 hour under vacuum, then cool to room temperature, and then filter using a 300-mesh gauze to obtain the adhesive.

[0050] The solder paste can be prepared by the following method: the high entropy alloy compound and the binder are mixed in a certain proportion, firstly, a vacuum planetary disperser is used to stir at a speed of 30-60rpm for 15 minutes, the prepared binder is stirred and foamed, and then the high entropy alloy compound is slowly and evenly sprinkled into the stirred binder, the stirring speed is 100-300rpm, the dispersion speed is 100-300rpm, after 2h of dispersion and mixing, the stirring speed is 60rpm, the dispersion speed is 500-1200rpm, and then vacuum degassing is performed, and filtering is performed with a 120-mesh gauze to obtain the solder paste.

[0051] S200: Solder paste is provided on the surface of the ceramic substrate.

[0052] According to some embodiments of the present application, in this step, solder paste is provided and disposed on the surface of the ceramic substrate. Specifically, providing the solder paste may include: providing a binder; dispersing the high entropy alloy compound in the binder to obtain the solder paste. For example, the components of the binder may be uniformly mixed to form a viscous liquid, and then the high entropy alloy compound may be uniformly dispersed in the viscous liquid by mechanical stirring or the like.

[0053] According to some embodiments of the present application, the process of setting the solder paste is not particularly limited. For example, the process of setting the solder paste may include screen printing, and the solder paste may be set on the surface of the ceramic substrate. The screen printing thickness is 6-25um, preferably 8-19um, and more preferably 10-15um.

[0054] S300: a copper layer is provided on the surface of the solder paste on the side away from the ceramic substrate.

[0055] According to some embodiments of the present application, in this step, a copper layer is arranged on the surface of the side of the solder paste away from the ceramic substrate, and the type of the copper layer is not particularly limited. For example, the copper layer can be a copper sheet, and the thickness of the copper sheet can be 0.1mm-5mm, preferably 0.3mm-1mm, the copper purity is 99.96%, preferably 99.99%, the copper grains are 8-25um, preferably 10-15um, and the copper layer can also be a high thermal conductivity copper-based composite material, a high thermal conductivity copper-based alloy, etc.

[0056] S400: Brazing process is performed to obtain a ceramic copper clad laminate.

[0057] According to some embodiments of the present application, in this step, the solder paste is brazed to obtain a ceramic copper clad laminate. The process of the brazing treatment is not particularly limited. For example, when a copper sheet is used as the copper layer, the brazing treatment can be a vacuum brazing treatment, wherein the temperature of the vacuum brazing treatment can be 850-1060°C, preferably 900-980°C, the time of the vacuum brazing treatment can be 30-180min, preferably 45-75min, the difference between the heating rate and the cooling rate is ≤15°C / min, preferably ≤10°C / min, and more preferably ≤3°C / min. In addition to using a vacuum brazing treatment, an inert gas can also be used, such as nitrogen, argon, hydrogen, vacuum + nitrogen / argon / hydrogen, etc., and the gas purity is preferably 99.999%. By using a vacuum brazing process for brazing treatment, the metal elements in the high entropy alloy compound and the copper sheet can be prevented from being oxidized.

[0058] Specifically, during the vacuum brazing process, mechanical pumps, roughing valves, Roots pumps, fore valves, diffusion pumps and main valves can be used to evacuate the furnace to a vacuum of 10-3Pa, and program heating can be performed. After the organic matter is fully removed, the temperature reaches the solidus of the high entropy alloy compound. After preheating, slowly heat up to the brazing temperature and maintain for a certain period of time to allow the weld to be fully and evenly heated, which is convenient for full wetting reaction during the brazing process. During the process of cooling from the brazing temperature to 600°C, the difference between the cooling rate and the heating rate is ≤5°C, and then the temperature is cooled with the furnace.

[0059] Specifically, the obtained ceramic copper clad laminate has a thermal resistance of less than 0.2℃*cm^ 2 / W, with few voids, peel strength greater than 20N / mm, and good reliability.

[0060] According to some embodiments of the present application, Figure 2 As shown, the above solder paste is used for preparation. After the ceramic copper clad laminate is etched through the solder layer, the ceramic does not turn black. Figure 3 Shown is a cross section of the solder layer on a ceramic copper clad laminate.

[0061] The scheme of the present application is described below by specific examples. It should be noted that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this area or the product instructions are used. The reagents or instruments used are not specified by the manufacturer, and are all conventional products that can be obtained commercially.

[0062] Example 1

[0063] 1. Preparation of binder: 88 wt% of solvent diethylene glycol butyl ether acetate is slowly added into an electromagnetic water bath, and slowly stirred at a speed of 30 rpm until the temperature rises to 80°C, and then 1.2 wt% of surfactant sodium dodecylbenzene sulfonate, 5 wt% of dispersant stearic acid, 3 wt% of thickener cyclodextrin, and 2.8 wt% of thixotropic agent hydrogenated castor oil are added into the solvent in sequence, and after each component is stirred at a speed of 300 rpm for 15 min, other components are added in sequence. After all components are added, stir and mix at a speed of 1200 rpm for 3 h, then evacuate the environment and stir at a speed of 500 rpm for 1 h. After stirring, cool to room temperature, filter using a 300-mesh gauze to obtain a binder.

[0064] 2. Preparation of solder paste: Cu 64.9 Al 15 Sn 12 Ni 0.9 P 0.2 Ti7 high entropy alloy is powdered, 87wt% of the high entropy alloy compound is added to 13wt% of the binder, firstly, it is stirred at a speed of 60rpm for 15min with a vacuum planetary disperser to stir and foam the prepared binder, and then the high entropy alloy compound is slowly and evenly sprinkled into the stirred binder, with a stirring speed of 120rpm and a dispersion speed of 300rpm. After 2h of dispersion and mixing, it is vacuumed and defoamed at a stirring speed of 60rpm and a dispersion speed of 800rpm, and filtered with a 120-mesh gauze to obtain a solder paste.

[0065] 3. Screen print the solder paste on one side of a 0.32mm ZTA ceramic sheet containing 6% zirconium oxide, and dry it at 120℃ for 15 minutes. Then screen print the solder paste on the other side of the ceramic sheet. Repeat the above steps. Cover the surface of the welding layer on both sides with 0.3mm thick oxygen-free pure copper. Place it in a vacuum brazing furnace for degreasing, debinding and sintering. The vacuum degree is 10 -3 Pa, pressure 30N, temperature 960℃ for 0.5 hours.

[0066] Example 2

[0067] This embodiment provides a solder paste and a ceramic copper-clad laminate, and the preparation method thereof is substantially the same as that of Embodiment 1, except that, in the preparation of the ceramic copper-clad laminate, a ZTA ceramic sheet containing 12% zirconium oxide is used.

[0068] Example 3

[0069] This embodiment provides a solder paste and a ceramic copper-clad laminate, and the preparation method thereof is substantially the same as that of embodiment 1, except that in the preparation of the solder paste, Cu 63.9 Al 15 Sn 12 Ni 0.9 P 0.2 Ti8 high entropy alloy was prepared.

[0070] Example 4

[0071] This embodiment provides a solder paste and a ceramic copper-clad laminate, and the preparation method thereof is substantially the same as that of embodiment 1, except that in the preparation of the solder paste, Cu 60.9 Al 15 Sn 12 Ni 0.9 P 0.2 Ti 11 The high entropy alloy was prepared.

[0072] Example 5

[0073] This embodiment provides a solder paste and a ceramic copper-clad laminate, and the preparation method thereof is substantially the same as that of embodiment 1, except that in the preparation of the solder paste, Cu 46.9 Al 15 Sn 12 Ni 0.9 P 0.2 Ti 25 In the preparation of ceramic copper-clad laminates, ZTA ceramic sheets containing 12% zirconium oxide are used.

[0074] Comparative Example 1

[0075] This comparative example provides a solder paste and a ceramic copper-clad laminate, and the preparation method thereof is substantially the same as that of Example 1, except that, in the preparation of the ceramic copper-clad laminate, a ZTA ceramic sheet containing 5% zirconium oxide is used.

[0076] Comparative Example 2

[0077] This comparative example provides a solder paste and a ceramic copper-clad laminate, and the preparation method thereof is substantially the same as that of Example 1, except that, in the preparation of the ceramic copper-clad laminate, a ZTA ceramic sheet containing 13% zirconium oxide is used.

[0078] Comparative Example 3

[0079] This comparative example provides a solder paste and a ceramic copper-clad laminate, the preparation method of which is basically the same as that of Example 1, except that in the preparation of the solder paste, Cu 41.9 Al 15 Sn 12 Ni 0.9 P 0.2 Ti 30 In the preparation of ceramic copper-clad laminates, ZTA ceramic sheets containing 12% zirconium oxide are used.

[0080] Comparative Example 4

[0081] This comparative example provides a solder paste and a ceramic copper-clad laminate, the preparation method of which is basically the same as that of Example 1, except that in the preparation of the solder paste, Cu 44.9 Al 15 Sn 12 Ni 0.9 P 0.2 Ti 27 The high entropy alloy was prepared.

[0082] Test method: The ceramic copper clad laminate is subjected to ultrasonic scanning test, peel strength test, hot and cold shock test, thermal resistance test, and blackened board break test. Among them, the defective rate of the ceramic copper clad laminate after welding is obtained by calculating the proportion of products with defective holes using the method in GB / T39240-2020 General Principles for Ultrasonic Testing of Nondestructive Testing; the peel strength of the ceramic copper clad laminate is tested using the GB / T11363-2008 brazing joint strength test method; the cold side impact test is to use a hot and cold shock box to conduct a hot and cold tolerance test in the temperature range of -55℃ to 150℃, where -55℃ and 150℃ stay for 30 minutes respectively, and the intermediate conversion is 15s. The peel strength and thermal resistance of 0 and 500 thermal shocks were tested; the thermal resistance test was carried out according to ASTM D5470 standard, the sample size was 2.7cm*2.7cm for copper surface and 2.8cm*2.8cm for ceramic surface, and the thermal resistance change rate could be measured. The thermal resistance change rate was the percentage increase or decrease of the thermal resistance of the ceramic copper clad laminate after 500 thermal shocks relative to the thermal resistance of the ceramic copper clad laminate without thermal shocks.

[0083] The blackening and broken board test method of the ceramic copper clad laminate is as follows: the ceramic copper clad laminate is patterned by the immersion method, and the copper is first etched by a solution of pH 4-6 prepared by NaClO3, HCl, and deionized water; then the solder layer is etched by an etching solution, such as GH-Ti-Etching BT etching solution, and the ceramic copper clad laminate is immersed in the etching solution for 4 hours until the ceramic leaks out of the etching groove, and then the ceramic copper clad laminate is taken out and washed with pure water and dried with hot air, and an optical microscope is used to observe whether the etching groove has a consistent color and is the color of ceramic, so as to judge whether the ceramic copper clad laminate is blackened, and record whether the pattern will break after etching during the transfer process, or observe whether the etching groove has cracks under an optical microscope, so as to judge whether the ceramic copper clad laminate is broken.

[0084] The test results are shown in Table 1 below:

[0085] Table 1

[0086]

[0087] 1) By comparing Example 2, Example 5 and Comparative Example 3, it can be seen that the Ti content of the high entropy alloy compound in the solder paste of Example 2 and Example 5 is 7% and 25% respectively, and the Ti content of the high entropy alloy compound in the solder paste of Comparative Example 3 is 30%. The experimental results in Table 1 show that the ceramic copper clad laminates corresponding to Example 2 and Example 5 did not break after etching; the ceramic copper clad laminate corresponding to Comparative Example 3 broke after etching.

[0088] 2) By comparing Examples 1, 3, 4 and Comparative Example 4, it can be seen that the Ti content of the high entropy alloy compound in the solder pastes of Examples 1, 3 and 4 is 7%, 8% and 11% respectively, and the Ti content of the high entropy alloy compound in the solder paste of Comparative Example 4 is 27%. The experimental results in Table 1 show that the ceramic copper clad laminates corresponding to Examples 1, 3 and 4 did not break after etching; the ceramic copper clad laminate corresponding to Comparative Example 4 broke after etching.

[0089] 3) By comparing Example 1, Example 2 and Comparative Example 1, Comparative Example 2, it can be seen that the ZTA ceramic sheets of Example 1 and Example 2 contain 6% and 12% zirconium oxide, respectively, and the ZTA ceramic sheets of Comparative Example 1 and Comparative Example 2 contain 5% and 13% zirconium oxide, respectively. The experimental results in Table 1 show that the ceramic copper-clad laminates corresponding to Example 1 and Example 2 did not turn black or break after etching; the ceramic copper-clad laminate corresponding to Comparative Example 1 broke after etching, and the ceramic copper-clad laminate corresponding to Comparative Example 2 turned black after etching.

[0090] In summary, the Ti content of the high entropy alloy compound in the solder paste is not less than 7% or not more than 25%, and the ceramic matrix includes 6%-12% zirconium oxide, which can prevent the ceramic matrix of the ceramic copper clad laminate from breaking and blackening after etching, improve the reliability of the ceramic copper clad laminate, reduce the thermal resistance of the ceramic copper clad laminate, and extend the service life of the ceramic copper clad laminate.

[0091] Unless otherwise specified, all scientific and technological terms used in this application have the same meaning as those commonly understood by those skilled in the art to which this application belongs. All patents and publications related to this application are incorporated herein by reference in their entirety. The term "comprising" or "including" is an open expression, i.e., including the content specified in this application, but does not exclude the content of other aspects.

[0092] The embodiments of the present application have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or improvements to the technology in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.

[0093] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A ceramic copper-clad laminate, characterized in that: The ceramic copper clad laminate comprises: The solder layer is made of solder paste, and the solder paste includes a high entropy alloy compound, and the chemical formula of the high entropy alloy compound is: Cu a Al b Sn c Ni d P e Mo f Ti g , wherein 7≤g≤25wt%, and a+b+c+d+e+f+g=100%; The ceramic matrix comprises 6% to 12% by mass of zirconium oxide.

2. The ceramic copper clad laminate according to claim 1, characterized in that: In the high entropy alloy compound, 35≤a≤65wt%, 10≤b≤35wt%, 10≤c≤25wt%, 0.1≤d≤10wt%, 0.05≤e≤3wt%, and 0≤f≤10wt%.

3. The ceramic copper clad laminate according to claim 1, characterized in that: The solder paste further comprises a binder, which comprises 75-98 wt % of a solvent, 0.1-20 wt % of a dispersant, 0.05-15 wt % of a thickener, 0.05-3 wt % of a surfactant and 0-10 wt % of a thixotropic agent.

4. The ceramic copper clad laminate according to claim 3, characterized in that: The solder paste satisfies any one of the following conditions: the solvent includes one or more of pineol, tributyl citrate, diethylene glycol butyl ether and diethylene glycol butyl ether acetate; the dispersant includes one or more of oleic acid, stearic acid and polyethylene glycol; the thickener includes one or more of ethyl cellulose, acrylic resin, cyclodextrin and alkane; the surfactant includes one or more of Tween 20, Span 80 and sodium dodecylbenzene sulfonate; the thixotropic agent includes one or more of polyamide wax, modified polyurea and hydrogenated castor oil.

5. The ceramic copper clad laminate according to claim 3, characterized in that: The mass fraction of the high entropy alloy compound in the solder paste is 60%-95%, and the mass fraction of the binder is 5%-40%.

6. The ceramic copper clad laminate according to claim 1, characterized in that: The melting point of the solder paste is in the range of 700-960° C., and the particle size of the solder paste is in the range of 0.3-60 um.

7. The ceramic copper clad laminate according to claim 1, characterized in that: The thickness of the ceramic substrate is 0.2-2 mm.

8. The ceramic copper clad laminate according to claim 1, characterized in that: It also includes a copper layer, which is made of a copper-containing material with a thickness of 0.1 mm to 5 mm. The copper-containing material is selected from one or more of a copper sheet, a high thermal conductivity copper-based composite material, and a high thermal conductivity copper-based alloy.

9. A method for preparing a ceramic copper-clad laminate, characterized in that: include: providing a ceramic substrate; Disposing solder paste on the surface of the ceramic substrate, wherein the solder paste includes a high entropy alloy compound; A copper layer is arranged on the surface of the solder paste on one side away from the ceramic substrate, and a brazing process is performed to obtain the ceramic copper-clad laminate.

10. The method according to claim 9, characterized in that The process of setting the solder paste on the surface of the ceramic substrate is screen printing, wherein the screen printing thickness of the solder paste set on the surface of the ceramic substrate by screen printing is 6-25um; The brazing process is a vacuum brazing process, wherein the temperature of the vacuum brazing process is 850-1060° C., and the time of the vacuum brazing process is 0.5-3 hours.

Citation Information

Cited By

  • Ceramic copper-clad laminate and preparation method therefor

    WO2026145128A1